The Effect of Asset Structure and Dividend Policy on the Capital Structure of Infrastructure Subsector Companies Listed on the Indonesia Stock Exchange 2016-2020 Period - Kusumawardhani, Aninditha Putri; Rizali, Ahmad Ramdan; Hadiantini, Ratih (International Journal of Research in Community Services, 2024)
The purpose of this study was to determine the effect of Asset Structure and Dividend Policy on the Capital Structure ofInfrastructures Sub-sector Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The research indicatorsused are Fixed Assets Ratio, Dividend Payout Ratio and Debt to Equity Ratio. The approach used in this research is a quantitativeapproach. The population in this study were 175 financial statements from 35 infrastructures sub-sector companies listed on theIndonesia Stock Exchange and the sample used in this study were 35 financial statements from 7 companies. The data used issecondary data, namely data obtained directly in the form of financial reports from the website of each company and thewww.idx.co.id website. The data analysis technique was carried out using statistical analysis, namely classical assumption test,multiple linear regression coefficient, multiple correlation coefficient, coefficient of determination and hypothesis testing usingSPSS version 25 program. The results showed that partially Asset Structure had no significant effect on The Capital Structure ofthe infrastructures subsector companies listed on the Indonesia Stock Exchange for the 2016-2020 period, while the DividendPolicy has no significant effect on the capital structure of the infrastructures subsector companies listed on the Indonesia StockExchange for the 2016-2020 period. Simultaneously, the Asset Structure and Dividend Policy have a significant influence on thecapital structure of the infrastructures sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period.